Three Characters Moulded in Music Education - Sutawi, Tyas Kartiko (Harmonia: Journal of Arts Research and Education, 2018)
Character building is an emerging issue in the education field. Character building in school is integrated through a learning process in each existing subject. Music education as one of the subjects in school, could mean to studentsÃ¢â‚¬â„¢ character building. It could be done through various musical activities which can be experienced directly by the students, one of them is an ensemble. The goal of this article is to reveal characters that could be developed through music education, especially ensemble. This research was done in a public senior high school in Yogyakarta by choosing three samples based on Proportional Stratified Random Sampling technique. The data was gathered by using questionnaire based on Exploratory Factor Analysis and Confirmatory Factor Analysis techniques. Reliability was counted by using Cronbach Alpha and Variance Reliability formula. Also, descriptive quantitative is used as a data analysis technique in this research. The result shows that there are three characters molded through music education at school, they are Ã¢â‚¬Å“rasaÃ¢â‚¬Â sensitivity, creativity and respect.